Risk Factors Evaluation in Vitamin D Deficient Population - Mujeeb Ur Rahman, Arooba Khan, Sajjad Mohammad, Bilal Ahmed, Muhammad Zubair, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Vitamin D concentrations often change with season, latitude, ethinicity, and diet composition. Proportion of the apparently healthy population may suffer from hypovitaminosis D. The purpose of this study is to investigate the prevalence and importance of vitamin D insufficiency, as well as the risk factors associated with it, in seemingly healthy persons. Materials and Methods: This was a survey-type research that took place between December 2013 and February 2014. Following their agreement, 100 people completed a questionnaire requesting demographics and clinical features of hypovitaminosis D. The vitamin D levels of 50 people were evaluated in the Excel Labs and Islamabad Diagnostic Center, Islamabad, Pakistan. Results: Data from 100 people was gathered. 25% are men and 75% are women. Questionaires were used to obtain information on their demographics, height, and weight. The threshold values for Vitamin D were 20 ng/mL inadequate, 21-29 ng/mL insufficient, and >30 ng/mL sufficient. It was discovered in 80% of the females and 71% of the men tested. Only 8% of those lacking in Vit. D had symptoms, whereas 92% had none. Conclusion: In conclusion, vitamin D insufficiency was widespread in our population. It is highly important to aware the health practitioners about the intervention techniques to rectify hypovitaminosis D. Keywords: Vitamin D, prevalence, NIH